KONTRIBUSI SEKTOR PERTANIAN TERHADAP PERTUMBUHAN EKONOMI DAN PENYERAPAN TENAGA KERJA DI KABUPATEN BARRU - Hasang, Ismail (Universitas Muhammadiyah Parepare, 2019)
This study aims to learn more about the agricultural sector on economic growth and employment in Barru Regency from 2012 to 2016. The method used in this research is quantitative descriptive research using statistical data. The results showed that (1) the contribution of the agricultural sector to economic growth in Barru District increased in 2012 to 2016, (2) the contribution of the agricultural sector in the development of labor in Barru District increased fluctuations from 2012 to 2016.